Valência dos verbos de conhecimento do português brasileiro - Janayna Maria da Rocha Carvalho (2012)
This is a descriptive work, and presupposes that before building thories, we should accumulate and systematize data with the aim of studying the relation between form and semantics. Starting from that, I attempt to present a description of knowledge verbs in Brazilian Portuguese. This description depends on the definition of conceptual thematic relations (RCT, its acronym in Portuguese) associated with verbs, and their syntactic expression in verbal complements. In general terms, a RCT corresponds to a frame element as defined by Ruppenhofer et al. (2006), that is, the semantic relation between a complement and the verb in its clause. It is a concept akin to the thematic role, but a RCT is less schematic, to the point of being accessible to direct intuition. A verb of knowledge is one that asserts something about the state of information in somebodys memory. Starting from that definition, we arrived to a sample of 22 verbs which are, exclusively or almost exclusively, used to represent the state of information in memory. There are other verbs in the language which, according to their object or in particular constructions, can also assert something about the state of information, but these verbs are not exclusive of this semantic field and were ignored in the analysis. Three RCTs were defined in relation to verbs of knowledge: Knower (Conhecedor), which is always expressed by the subject; Thing known (Coisa conhecida), expressed by the object or by a prepositional phrase tradicionally termed indirect object; and Source of knowledge (Origem do conhecimento), expressed by a prepositional phrase, traditionally termed adjunct. The first of these RCTs is always expressed; the second RCT may be omitted; and the third one follows a restriction which has to do with the Aktionsart of the verb. More specifically, the Source of knowledge appears only in connection with verbs of accomplishment or achievement (cf. Vendler, 1967). Finally, I make some approximations between the RCTs defined here and the thematic roles current in the literature. Following Perinis (2008) criteria, I do not identify the Knower as a case of Experiencer (contra Britto et al., 2002; Cavalho, 2008; Eluseu, 2010), because this thematic role can be expressed by an object, whereas the Knower cannot. I also found that the RCT Knower is associated to the subject of some perception verbs like notar, ver, perceber, all related to the entry of information into memory; and I explore some hypotheses on the definition of thematic roles from RCTs, to be developed in future work.